Penerapan Metode Qowaid Wa Tarjamah Dalam Meningkatan Maharah Qiro’ah (Ketrampilan Membaca) Pembelajaran Bahasa Arab Siswa Kelas VII D MTsN 5 Kediri - Eni Ernawati (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
The lack of interest in student learning and the lack of students in the process of learning Arabic in the classroom, especially in the achievement of maharah qiro'ah at a low level of student learning outcomes, then problems arise because of the inaccuracy of the methods used by teachers in teaching or often called the use of methods that touch students.. This research is a Class Action Research (PTK) as many as 2 cycles, in each cycle stages are carried out. In the precyclical, pay attention to the data of student observation results with the technique of using questionnaires / interviews and found results that did not reach the Minimum Completeness Creteria (KKM), then improvements were made with two cycles by going through the stages of planning and preparation, implementation, observation (observation), and reflection. From the results of learning improvements that have been carried out through two cycles, it can be concluded that the application of the Qowaid Wa Tarjamah method can improve the learning outcomes of class VII D MTsN 5 Kediri students in arabic language learning, especially maharah qiro'ah. Before the application of the Qowaid Wa Tarjamah method in the pre-cycle of student learning outcomes 68 on average with a percentage of completion of 60%, after applying the Qowaid wa Tarjamah method in the first cycle, the average student outcome rose to 80 with a percentage of 86.6%, because the results have not reached KKM, then another cycle 2 research is carried out, in cycle 2, student results can reach KKM after getting a more detailed understanding of maharah qiro'ah, and results can achieve a complete score of 100% with the average student score.